The Effect of Compensation and Rewards on Employee Performance of Pt. Hasjrat Multifinance - Ghifary, Adhifa Mizan; Syamlan, Adiba Fuad (Maneggio, 2024)
Compensation and rewards are important aspects to improve employee performance. Compensation is an individual driver in carrying out activities and providing good results. The awards given will spur employees' enthusiasm in working to achieve the company's goals. The purpose of the study was to determine the influence of compensation and rewards on employee performance. The population in this study is all employees of PT. Hasjrat Multifinance. Sampling was carried out by simple random sampling. The number of samples in this study was 115 respondents. The results obtained Compensation had a positive and partially significant influence on Employee Performance with a tcount of 3.113 > ttable 1.65845 and a significance of 0.002 < 0.05. The award had a negative and negative effect on Employee Job Satisfaction as evidenced by the Tcount test result score of 3.963 < Ttable 1.65845 and significance of 0.000 < 0.05. Furthermore, Compensation and Awards have a positive and significant effect simultaneously on the variables bound by Employee Performance. This result was obtained from the results of Fcal 12,980 > Ftable 3.08 and 0.000 < 0.05 The influence of both Compensation and Reward on the Employee Performance variable was 18.8%. Furthermore, the other 81.2% were influenced by other factors.